Harnessing the Power of AI in Shaping Administrative Law Regulations - Fatria Khairo; Firman Freaddy Busroh (International Journal of Science and Society, 2023)
The rapid and transformative advancements in Artificial Intelligence (AI) have reached a pivotal juncture, necessitating a re-evaluation of the regulatory frameworks in various sectors, including administrative law. This paper delves into the potential of AI in shaping administrative law regulations. While the inherent computational abilities of AI allow for processing vast amounts of data, providing real-time insights, and predicting administrative needs, they also introduce challenges related to ethics, transparency, and accountability. By analyzing global best practices and case studies, this paper highlights the dual-edged nature of AI, where on one side, it can aid in making more informed regulatory decisions, reduce bureaucratic inefficiencies, and improve citizen engagement. On the other side, unchecked use can lead to biases, opaque decision-making, and potential encroachments on individual rights. The paper concludes by proposing a balanced approach that harnesses the potential of AI while ensuring ethical and transparent use in the realm of administrative law.